2001
DOI: 10.1038/sj.bjp.0704180
|View full text |Cite
|
Sign up to set email alerts
|

An alternative pathway for metabolism of leukotriene D4: effects on contractions to cysteinyl‐leukotrienes in the guinea‐pig trachea

Abstract: 1 Contractions of guinea-pig tracheal preparations to cysteinyl-leukotrienes (LTC 4 , LTD 4 and LTE 4 ) were characterized in organ baths, and cysteinyl-leukotriene metabolism was studied using radiolabelled agonists and RP-HPLC separation. 2 In the presence of S-hexyl GSH (100 mM) the metabolism of [ (1 ± 10 nM) with a pA 2 -value of 9.3+0.2. However, at higher concentrations of ICI 198,615 (30 ± 300 nM) a residual contraction to LTD 4 was unmasked, and this response was inhibited by BAY u9773 (1 ± 3 mM). 4 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This is in agreement with a previous study showing a difference in the antagonist sensitivity between LTC 4 and LTD 4 in gastric smooth muscle cells and suggests that both CysLT 1 and CysLT 2 might mediate leukotriene-induced contraction not only in the antrum but also in the fundus (DeLegge et al, 1993;Bäck et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with a previous study showing a difference in the antagonist sensitivity between LTC 4 and LTD 4 in gastric smooth muscle cells and suggests that both CysLT 1 and CysLT 2 might mediate leukotriene-induced contraction not only in the antrum but also in the fundus (DeLegge et al, 1993;Bäck et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Tetrodotoxin was obtained from Tocris Cookson, Avonmouth Bristol, UK. L-serine borate was prepared from L-serine and boric acid solutions and buffered at pH 7.4 with NaOH (Bäck et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C). Previous reports showed functional antagonism of Bay-u9773 to the contraction activities of CysLT2 in organ bath assay of guinea pig (18,19). We showed that Bay-u9773 behaved as an antagonist and a partial agonist for gpCysLT2 in intracellular calcium response as well as other species (23) and that Bay-u9773 induced cellular proliferation by itself and with the following stimulation of LTC4.…”
Section: Intracellular Calcium Elevation Through Gpcyslt2mentioning
confidence: 63%
“…Based on functional smooth muscle studies, it was reported that gpCysLT2 was expressed in the ileum (18) and trachea (19). We investigated the tissue distribution of guinea pig CysLT2 gene by quantitative real time PCR (Fig.…”
Section: Tissue Distribution Of Gpcyslt2 Expressionmentioning
confidence: 99%